HYDROTHERMAL DISCHARGE AND THE THERMAL FIELD OF THE BAIKAL RIFT ZONE - Golubev V.A. (My University, 1988)
The contradiction between the relatively low regional heat flow observed in the Baikal rift area and the absence of anomalously heated matter at the Mohorovicic discontinuity was previously explained in terms of the unsteadiness of the geothermal field. According to previous calculations that neglected the convective heat transport by hydrothermal water, the source of anomalous heat under the crust of the rift zone appeared relatively recently, i.e., a few million years ago, and the heat flow that it produced has only partially reached the earth's surface. Correction for the hydrothermal discharge lead us to a revision of this conclusion. Thus, high temperatures close to the melting temperatures of the rocks can also exist at the base of the crust in the Baikal rift zone in the case of a steady-state temperature field. The redistribution of heat by subsurface waters apparently also explains the low heat flows observed in the mountain fringes of the rift valleys in other conventional rift zones.